2000
DOI: 10.1080/00034980050006447
|View full text |Cite
|
Sign up to set email alerts
|

Specific and total IgE in patients with recurrent, acute urticaria caused by Anisakis simplex

Abstract: Titres of parasite-specific IgE were investigated in 19 patients thought to have recurrent, acute urticaria caused by sensitization to Anisakis simplex (Dujardin, 1845), before and after they were placed on a fish-free diet. Patients with other allergic disease and those being treated with corticosteroids or antihistaminics were excluded. Skin-prick tests were carried out with A. simplex extract, and blue- and white-fish extracts. The CAP system (Pharmacia), a commercial test kit developed for the assay of foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Second, we did not confirm the Anisakidae larvae histopathologically. Immunologic methods using specific serum IgE antibody to A. simplex are reported to be helpful in the diagnosis of anisakiasis, but this antibody was detected in 25% of healthy controls and lacked specificity because of its cross-reactivity with other parasite antigens [ 23 ]. Furthermore, it is not generally available; thus, we could not utilize it in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we did not confirm the Anisakidae larvae histopathologically. Immunologic methods using specific serum IgE antibody to A. simplex are reported to be helpful in the diagnosis of anisakiasis, but this antibody was detected in 25% of healthy controls and lacked specificity because of its cross-reactivity with other parasite antigens [ 23 ]. Furthermore, it is not generally available; thus, we could not utilize it in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A. simplex can cause direct tissue damage following larval invasion in the gut wall, development of an eosinophilic granuloma, or perforation of the gut [1,2]. It has also been reported that an A. simplex larval infection can cause an allergic response due to anti- Anisakis IgE antibodies [3-5]. The allergic responses caused by anisakiasis include anaphylaxis, urticaria, angioedema, rheumatic manifestations, and nephrotic syndrome [6-11].…”
mentioning
confidence: 99%